The Role of Latvian Catholic Church Textiles in Perfecting People’s Aesthetic Values - Jansone, Aija (Acta humanitarica academiae Saulensis, 2019)
Under the National Research Program “Letonika” in University of Latvia, the scientific topic “The Role of Latvian Catholic Church Textiles in Perfecting People’s Aesthetic Values” was started. In the frame of the project, the author has begun to identify the textiles in Catholic churches in Latgale, paying special attention to the raw materials and handicraft techniques used in their making that had a special role in increasing people’s cultural and living standards.The material collected in churches is very diverse. It shows many layers of culture, different materials, techniques and adornments.According to functionality, Catholic liturgical vestments can be classified as follows: the liturgical clothing of priests (clergy attire) and interior textiles of the church (altar cover, flags, baldachin, etc.). According to the techniques of the material and performance applied, liturgics textile fabrics may be divided into: colored liturgics textiles and white liturgics textiles.The author’s special interest was caused by the likeness of alb and surplice to the cut of peasants’ shirts. Phenomenally, that worldwide straight thread cut and traditional crosscutting technology of the cut of alb and surplice has survived until now. However, among peasants this cut of shirts disappeared at the turn of the 20th century.In the 19th century, there was mutual influence in church and peasant textiles. Namely, the church used local materials in the making of liturgics textiles (fine linen fabrics were in great respect) and traditional shirt cuts that have been recognized for many generations, but the peasants (through the church) became aware of new raw materials, craft materials, artwork machinery and compositions. Perhaps the peasants of the church took advantage of techniques such as open work, embroidered net, crochet laces, Richelieu and English embroidery, with which the ordinary people willingly embroidered their clothing and room textiles.The decorated church’s textiles encouraged the peasants to learn new crafts, to make their clothing and interior designs more beautiful and timely. New needlework knowledge improved the cultural level of the nation, raised awareness of the beauty and timeliness, and provided insight into art trends in Europe. At the same time, the pursuit of everything new, methodically led to a reduction in the specificity of traditional lifestyle.
Keywords: liturgical textiles; materials; techniques; adornments; alb; surplice